Does a mandatory 36-to-48-hour later assessment for sport-related concussions reduce the risk of athletes inappropriately returning to play? - Griffin, S.; Cross, M.; Henderson, L.; Jones, G. A.; Stokes, K.; Kemp, S. (British Journal of Sports Medicine, 2021)
Background Concussion is one of the key player welfare issues in rugby union. A post-match assessment is a mandatory part of the head injury assessment (HIA) process in elite men`s rugby union, something unique to the sport and not seen in many other sporting settings. There is little evidence surrounding the potential value of this mandatory post-match assessment.